Species composition and distribution of Sponges in some islands in Vietnam sea - Do, Cong Thung (Vietnam Journal of Marine Science and Technology, 2024)
Research results from 2003 to present, in same Vietnamese islands, have identified 205 Sponges species belonging to 85 genera and 56 families, 22 orders of 3 classes, including Dermospongia class (203 species), two classes Calcarea and Homoscleromorpha has only 1 species in each class. Among these, there are 3 species new to science: Cladocroce pansinii Bertolino & Calcinai, 2023, Cladocroce lamellata Bertolino and Calcinai, 2023 and Spongilla marconii. The diversity of Sponges is quite high, reaching 2.4 species/genus, 3.66 species/family and 9.32 species/order. Orders with the highest number of species include Haplosclerida (55 species), followed by Poecilosclerida (29 species), Dictyoceratida (21 species), and Halichondrida (20 species). The South Central islands have the highest number of species (121 species), followed by the North Central islands (65 species), the Northeastern islands of Vietnam (57 species), Spratly Islands (37 species) and Phu Quoc (15 species). Species Cinachyrella australiensis, Dysidea fragilis, Dysidea cinerea can live at a water depth of 134 m. The biomass of Sponges varies from 0.14–2.5 kg/m2.